Calcaneal Inferior Spur Fracture Obvious but Easily Missed - Musa, Ahmedelmustafa A; Al-Taie, Alaa A (Archives of Clinical and Medical Case Reports, 2022)
Calcaneal inferior spurs are bony outgrowth that can arise from multiple sites. Compressive and traction forces are theorized to be the etiology behind their genesis. Blunt trauma to the plantar aspect of the foot can lead to calcaneal inferior spur fracture. We present a case of a 38-years-old male presenting inability to bear weight on his left foot with point tenderness after falling from a 3-meters height. Radiographic examination revealed fracture of calcaneal inferior spur, from which the patient was conservatively treated successfully. Fracture inferior calcaneal spur is a rare cause of heel pain. The reviewed literature showed how both conservative and surgical managements are used, the former more frequently.